Somewhere [videorecording (DVD)] - Coppola, Sofia, 1971-; Coppola, Sofia, 1971-; Coppola, Sofia, 1971-; Fanning, Elle, 1998-; Dorff, Stephen, 1973- (Universal, 2011)
A witty, moving, and empathetic look into the orbit of actor Johnny Marco. You have probably seen him in the tabloids; Johnny is living at the legendary Chateau Marmont hotel in Hollywood. He has a Ferrari to drive around in, and a constant stream of girls and pills to stay in with. Comfortably numbed, Johnny drifts along. Then, his 11-year-old daughter Cleo from his failed marriage arrives unexpectedly at the Chateau. Their encounters encourage Johnny to face up to where he is in life.